2009
DOI: 10.1089/jir.2009.0010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cholesterol Involvement in Src, PKC, and p38/JNK Transduction Pathways by Porins

Abstract: Biological membranes are described as a mosaic of different domains where interactions between membrane components induce the formation of subdomains with different characteristics and functions. Lipids play an important role in the formation of lipid-enriched microdomains where they dynamically associate to form platforms important for membrane protein sorting and construction of signaling complexes. Cholesterol confined in lipid domains is a crucial component required by microorganisms, directly or indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Therefore, it is likely that the macrophage membrane is the main target for the binding and action of ChoD. It has also been documented by others [21] that intact cholesterol in the monocyte membrane is required for activation of intracellular signaling proteins (e.g., p38 MAPK) in these cells. We found that macrophages treated with ChoD release significant amounts of the anti-inflammatory cytokine IL-10, which inhibits the synthesis of proinflammatory cytokines such as interferon- γ , tumor necrosis factor- α , IL-2, and IL-1.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, it is likely that the macrophage membrane is the main target for the binding and action of ChoD. It has also been documented by others [21] that intact cholesterol in the monocyte membrane is required for activation of intracellular signaling proteins (e.g., p38 MAPK) in these cells. We found that macrophages treated with ChoD release significant amounts of the anti-inflammatory cytokine IL-10, which inhibits the synthesis of proinflammatory cytokines such as interferon- γ , tumor necrosis factor- α , IL-2, and IL-1.…”
Section: Discussionmentioning
confidence: 87%
“…For example, both JNK [33] and p38 MAP kinases [34] were previously suggested to take part in membrane-associated HSP25 induction. Of note, cholesterol depletion inhibited JNK and p38 MAP kinase-associated signaling in different model systems [35,36]. Thus, it is tempting to speculate that MβCD-or nystatin-induced PM modifications impair different signaling cascades towards HSF1 resulting in an altered PTM profile.…”
Section: Discussionmentioning
confidence: 99%